The Development of Listening Assessment Tool for X Class Senior High School in Magelang - Setianingsih, Trisna Dwi (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2018)
This research aims to (1) describe the students and teachers characteristic requirement to the listening assessment tool, (2) to build a listening assessment tool prototype, (3) to present the expert test result, and (4) to describe the effectiveness of the web-based listening assessment tool to X class of Senior High School in Magelang. This research uses Research and Development (R & D) approach. The Data collection techniques used in this research are: observation, documentation, interviews, and questionnaires. The result of the research is to create a listening assessment tool that can be accessed online by students using laptop, computer, or smartphone through access http://www.nyemakbasajawa.com. The Web tools generated in this research is an instructional assessment tools for X class senior high school, the assessment tool consist of crita cerkak, pawarta text, and descriptive text of Javanese traditional house. The assessment tool has got validation from experts in this material and graphic/media experts, and has been successfully tested to the target students. The validation and test results show that the assessment listening tool has been qualified and effectively used as an assessment tool for learning Javanese in X class senior high school.